Peluang dan Tantangan Bank Syariah di Era Industri 4.0 - Rifqy Tazkiyyaturrohmah; Endang Sriani (Transformasi : Jurnal Studi Agama Islam, 2020)
Nowadays the industrial world is entering a new era called Industrial Revolution 4.0. The implementation of the fourth generation industry must be followed by the establishment of a healthy and sustainable ecosystem in order that it might be effective and able to drive all sectors, particularly economic and business sectors in Indonesia. The phenomenon of fintech is the delivery of product and financial services through the technological platform and innovative business model. In the Industrial Revolution 4.0, creative economic actors and Sharia financial institution should be able to think creatively and optimally to face all the challenges and opportunities created from this era. This research is a qualitative study using a descriptive approach, with the intention of interpreting phenomena that occur and is carried out by involving various existing methods. The results of this study, that there are several opportunities and challenges faced by Islamic banks in Indonesia in facing the 4.0 industrial revolution in the scope of financial technology (fintech). The main challenge facing sharia banks in facing the industrial revolution4.0 is how to develop products and services to spur productivity and competitiveness in the economic and business industries. As for the opportunities owned by Islamic banking to develop products and services to deal with industry 4.0, namely, firstly qualified human resources, secondly technological sophistication, thirdly products needed by the community in the face of the industrial revolution 4.0.